ANALISIS PENGARUH LOKASI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MINYAK GORENG BIMOLI PADA TOKO SULAWESI KAB. MAJENE - Muhammad Rezky Naim (POLITEKNIK LP3I JAKARTA, 2022)
This research is entitled Analysis of the Effect of Location and Price on the Purchase Decision of Cooking Oil at the Sulawesi Shop, Kab. Majene and the formulation of the problem expressed in this study is how the influence of location on the decision to purchase Bimoli cooking oil at the Sulawesi shop, Kab. Majene, How is the Price of Bimoli Cooking Oil Purchase Decision at the Sulawesi Shop, Kab. Majene and which variable has a more dominant influence on the Purchase Decision of Bimoli Cooking Oil at the Sulawesi Shop, Kab. Majene while the purpose of this study is to analyze the influence of location on the decision to purchase Bimoli cooking oil at the Sulawesi shop, Kab. Majene, to analyze the effect of price on the decision to purchase Bimoli cooking oil at the Sulawesi shop, Kab. Majene and To analyze which variable has a more dominant influence on the Purchase Decision of Bimoli Cooking Oil at the Sulawesi Shop, Kab. Majene. The population in this study are consumers of Sulawesi Stores, Kab. Majene with infinite population. The number of variables is 2, then the minimum number of samples is 50 people while the analytical method used in this study is to use Validity Value Testing and Reliability Value Testing, Multiple Regression Equation Results, t-value testing and F-value testing. While the results found in this study is Location (X1) has a significant effect on the Dependent Variable of Bimoli Cooking Oil Purchase Decision (Y) at the Sulawesi Shop, Kab. Majene, Price (X2) has a significant effect on the Dependent Variable Purchase Decision of Bimoli Cooking Oil (Y) at the Sulawesi Shop, Kab. Majene and (X1) have a more significant effect on the Purchase Decision of Bimoli Cooking Oil (Y) at the Sulawesi Shop, Kab. Majene.Keywords: Location, Price, Purchase Decision